Accounting for Financial Instruments in the Banking Industry: Conclusions from a Simulation Model - Günther Gebhardt; Rolf Reichardt; Carsten Wittenbrink (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
The paper analyses the effects of three sets of accounting rules for financial instruments - Old IAS before IAS 39 became effective, Current IAS or US GAAP, and the Full Fair Value (FFV) model proposed by the Joint Working Group (JWG) - on the financial statements of banks. We develop a simulation model that captures the essential characteristics of a modern universal bank with investment banking and commercial banking activities. We run simulations for different strategies (fully hedged, partially hedged) using historical data from periods with rising and falling interest rates. We show that under Old IAS a fully hedged bank can portray its zero economic earnings in its financial statements. As Old IAS offer much discretion, this bank may also present income that is either positive or negative. We further show that because of the restrictive hedge accounting rules, banks cannot adequately portray their best practice risk management activities under Current IAS or US GAAP. We demonstrate that - contrary to assertions from the banking industry - mandatory FFV accounting adequately reflects the economics of banking activities. Our detailed analysis identifies, in addition, several critical issues of the accounting models that have not been covered in previous literature.
urn:nbn:de:hebis:30-10269
Keywords: G21; M41; 330; Accounting for Banks; Bank Simulation; Fair Value Accounting; Financial Instruments; Hedge Accounting; IAS; US GAAP